Mental health, study skills, social support, and barriers to seeking psychological help among university students: a call for mental health support in higher education - Hyseni Duraku, Zamira; Davis, Holly; Hamiti, Era (Frontiers in Public Health, 2023)
Introduction: Poor mental health among youths is a complex worldwide issue. Many countries with medium-to-low levels of development, particularly those in Southern Europe, have not introduced appropriate mental health and educational strategies to identify the key factors influencing well-being, promote psychological well-being, and prevent poor mental health among youths. In response to these trends, we sought to uncover insights for developing interventions for youth mental well-being. We assessed mental health, study skills, barriers to seeking psychological help, and perceived social support among Kosovar university students, and investigated their experiences with professional mental health services and their needs and perceptions regarding the importance of professional mental health services on campus. Methods: The study used a parallel mixed-methods design. Participants included 234 university students. Quantitative data were gathered through validated questionnaires, including the Depression, Anxiety, and Stress Scale, Multidimensional Scale of Perceived Social Support, Academic Anxiety Scale, Study Skills Assessment Questionnaire, and the Barriers to Seeking Psychological Help Scale. Qualitative data on the students’ experiences with mental health services and their perceptions regarding the importance of professional university mental health services were explored through open-ended questions. Results: Most students experienced anxiety and depression, more than half were stressed, and most reported poor or moderate study skills. Lack of trust in mental health professionals was a major barrier to seeking psychological help, followed by difficulties in self-disclosure. Perceived social support and academic anxiety were significant predictors of barriers to seeking psychological help. The participants believed that mental health and academic support from the university would help improve their mental well-being, study skills, self-esteem, self-perception, and attitudes toward social support; raise awareness regarding mental health; and help them overcome personal and academic challenges. Discussion: Our findings highlight the need for more comprehensive and accessible mental health services on campuses. By providing adequate support and resources to address various personal and academic factors that contribute to mental health issues in university students, universities can enhance students’ academic success and personal growth.